Composición florística y estructura del bosque húmedo tropical del refugio de vida silvestre marino costero Pacoche. año 2018 - Gaona Ochoa, Telmo Galecio (2019)
Seasonal research piemontano was held in the evergreen forest, located in the parish of San Lorenzo Canton Manta; Wildlife Refuge Coastal Sea in "Pacoche”, belonging to the Heritage of Natural Areas of the State (PANE), located in the parish of San Lorenzo canton Manta. The objective of this investigation was to evaluate the diversity and tree structure ≥ to 10 cm D1,30 m, its endemism and the state of conservation of the present species, in addition the most potential species were determined for reforestation programs of the Refuge, in permanent transects of 1000 m2 of forest. 32 species, 27 genera and 21 botanical families were recorded, the most abundant family was the Moraceae with 5 species, the most abundant and ecologically important species were Inga edulis and Myriocarpa stipitata, the 5 sampling units had an average diversity, according to the Shannon index and a high diversity according to the Simpson index and, the greater similarity was between transects 3 and 4, with a percentage value of 14.7541, the structure of the forest presented a distribution of an "inverted J", that is to say that individuals are abundant in the first categories, presenting a young distribution of the forest; it was recorded that Phytelephas aequatorialis, it presents national endemism and, according to the category of threat, the species with the greatest risk are: Cedrela odorata (VU),Phytelephas aequatorialis and Bactris setulosa (NT), Mauria heterophylla , Cordia alliodora, Cordia collococca and Maclura tinctoria (LC). Keywords: diversity, structural parameters, evergreen forest, endemism, threat category